Hysteretic Energy-Based Estimation of Ductility Demand in Single Degree of Freedom Systems - Hancioglu, Baykal; Kircil, Murat Serdar; Polat, Zekeriya (MDPI, 2025)
Ductility, as a fundamental mechanical property, allows structures to undergo inelastic deformations and dissipate seismic energy while maintaining their load-carrying capacity without substantial strength degradation. Thus, the estimation of structural ductility demand has consistently constituted an essential topic of research interest in earthquake engineering. In this study, an iterative procedure for estimating the ductility demand of elastoplastic single-degree-of-freedom (SDOF) systems through dissipated energy is introduced. The proposed procedure helps the determination of ductility demand by use of only elastic response spectra. It initially estimates the hysteretic energy as a proportion of the total input energy. Then, ductility demand is estimated with the help of a developed equation by performing regression analyses based on the nonlinear time history analyses results of elastoplastic single-degree-of-freedom (SDOF) systems with a certain strength. Time history analyses were carried out by using an extensive earthquake ground motion database, which includes a total of 268 far-field records, two horizontal components from 134 recording stations located on firm soil sites.
Keywords: input energy; hysteretic energy; ductility demand; hysteretic energy ratio; INELASTIC DISPLACEMENT RATIOS; SEISMIC ENERGY; DESIGN; SPECTRA; INPUT; Construction & Building Technology; Engineering